Predictors of in‐school and out‐of‐school sport injury prevention: A test of the trans‐contextual model. (26th September 2020) - Lee, Alfred S. Y.; Standage, Martyn; Hagger, Martin S.; Chan, Derwin K. C.
Abstract: The current study aimed to predict secondary school students' motivation toward sport injury prevention in "in‐school" and "out‐of‐school" contexts, and their sport injury prevention behavior at 3‐month follow‐up using the trans‐contextual model (TCM). Hong Kong secondary school students (N = 1566; mean age = 13.34 years, range = 11 to 19; female = 49.42%) were recruited. Participants were asked to complete a survey comprising previously validated scales measuring TCM constructs at baseline and a measure of sport injury prevention behavior at follow‐up three months later. Structural equation modeling (SEM) was used to examine the hypothesized paths among TCM constructs. A SEM specifying hypothesized paths among TCM variables showed acceptable fit with the data (χ 2 (29) = 418.55, CFI = .93, TLI = .90, and RMSEA = .09, 90% CI [.09, .10], and SRMR = .05). Findings supported tenets of the TCM: the effects of perceived autonomy support from PE teachers on in‐school autonomous motivation toward injury prevention, the trans‐contextual relationship between students' "in‐school" and "out‐of‐school" autonomous motivation toward injury prevention, and the effects of autonomous motivation toward injury prevention on social cognitive variables and subsequent sport injury prevention behaviors. Results supported the tenets proposed within the TCM in predicting students' "in‐school" and "out‐of‐school" autonomous motivation toward sport injury prevention. Findings underscore the potential importance of autonomy support from PE teachers in facilitating students' sport injury prevention behaviors. Further longitudinal and intervention research is warranted to establish temporal and causal effects of TCM variables in sport injury prevention.